2015
DOI: 10.1088/0004-637x/807/2/127
|View full text |Cite
|
Sign up to set email alerts
|

NEW NEAR-INFRARED PERIOD–LUMINOSITY–METALLICITY RELATIONS FOR RR LYRAE STARS AND THE OUTLOOK FORGAIA

Abstract: We present results of the analysis of 70 RR Lyrae stars located in the bar of the Large Magellanic Cloud (LMC). Combining spectroscopically determined metallicity of these stars from the literature with precise periods from the OGLE III catalogue and multi-epoch K s photometry from the VISTA survey of the Magellanic Clouds system (VMC), we derive a new near-infrared period-luminosity-metallicity (PL K s Z) relation for RR Lyrae variables. In order to fit the relation we use a fitting method developed specifica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
115
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(131 citation statements)
references
References 72 publications
15
115
0
1
Order By: Relevance
“…The B-W absolute magnitudes were taken from the compilations in Table 11 of Cacciari et al (1992) and Table 16 of Skillen et al (1993) and revised, first assuming for the p factor used to transform the observed radial velocity to true pulsation velocity the value p = 1.38 proposed by Fernley (1994) 6 , and then averaging multiple determinations of individual stars. We note that the K-band magnitudes of RR Lyrae stars analysed with the B-W method are in the Johnson photometric system; however, the difference between the 2MASS K s and the Johnson K is small, about 0.03 mag on average, for the typical colour of RR Lyrae stars (Muraveva et al 2015) and is always much smaller than the individual errors in the B-W M K magnitudes. We have transformed the B-W absolute magnitudes to photometric parallaxes.…”
Section: Comparison With Baade-wesselink Studiesmentioning
confidence: 64%
See 4 more Smart Citations
“…The B-W absolute magnitudes were taken from the compilations in Table 11 of Cacciari et al (1992) and Table 16 of Skillen et al (1993) and revised, first assuming for the p factor used to transform the observed radial velocity to true pulsation velocity the value p = 1.38 proposed by Fernley (1994) 6 , and then averaging multiple determinations of individual stars. We note that the K-band magnitudes of RR Lyrae stars analysed with the B-W method are in the Johnson photometric system; however, the difference between the 2MASS K s and the Johnson K is small, about 0.03 mag on average, for the typical colour of RR Lyrae stars (Muraveva et al 2015) and is always much smaller than the individual errors in the B-W M K magnitudes. We have transformed the B-W absolute magnitudes to photometric parallaxes.…”
Section: Comparison With Baade-wesselink Studiesmentioning
confidence: 64%
“…1, coefficients and zero point of the relation differ significantly; the literature values for the dependence of M K s on period range from −2.101 (Bono et al 2003) to −2.73 (Muraveva et al 2015) and the dependence on metallicity ranges from 0.03 (Muraveva et al 2015) to 0.231 (Bono et al 2003). We used the sample of 200 RR Lyrae stars with TGAS parallaxes along with K s magnitudes, period, and metallicity values from Dambis et al (2013) to fit the PM K s and PM K s Z relations.…”
Section: Derivation Of the Rr Lyrae Stars Pl And Plz Relations In Thementioning
confidence: 93%
See 3 more Smart Citations